1998
DOI: 10.1002/(sici)1097-0347(199801)20:1<8::aid-hed2>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of p53 abnormalities at the invasive front of oral squamous cell carcinomas

Abstract: Background The prognostic significance of the invasive tumor front in squamous cell carcinomas has recently been recognized. The aim of the present study was to investigate possible molecular mechanisms underlying the significance of this area in oral squamous cell carcinomas. Methods We used immunohistochemical and molecular genetic techniques to investigate whether p53 alterations at the invasive tumor front could determine the aggressiveness of oral cancers. Results p53 Overexpression was detected in 52% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
8

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
(30 reference statements)
3
27
0
8
Order By: Relevance
“…La vaste majorité des études portant sur p53 dans les cancers ORL ont examiné soit l'expression protéique (reflet indirect de l'état muté) ou le statut géné-tique [15]. La plupart des études n'ont pas permis de mettre en évi-dence une valeur pronostique forte de l'expression tumorale ORL en p53 que ce soit à partir de la tumeur elle-même [7][8][9][10][11][12][13][14][15][16] ou du front invasif tumoral [17]. De même, l'examen des corrélations entre le pronostic des tumeurs ORL et les mutations p53 (exons 5-9) ne permet pas de conclure fermement avec des étu-des supportant une valeur prédic-tive défavorable de p53 mutée [11] et d'autres pas [14].…”
Section: La Protéine P53unclassified
See 1 more Smart Citation
“…La vaste majorité des études portant sur p53 dans les cancers ORL ont examiné soit l'expression protéique (reflet indirect de l'état muté) ou le statut géné-tique [15]. La plupart des études n'ont pas permis de mettre en évi-dence une valeur pronostique forte de l'expression tumorale ORL en p53 que ce soit à partir de la tumeur elle-même [7][8][9][10][11][12][13][14][15][16] ou du front invasif tumoral [17]. De même, l'examen des corrélations entre le pronostic des tumeurs ORL et les mutations p53 (exons 5-9) ne permet pas de conclure fermement avec des étu-des supportant une valeur prédic-tive défavorable de p53 mutée [11] et d'autres pas [14].…”
Section: La Protéine P53unclassified
“…Selon la valeur du REGF initial la survie globale des répondeurs était modifiée : alors que les répondeurs complets avaient une survie significativement plus longue que les répondeurs partiels et les non-répondeurs, l'introduction du REGF modifiait ce tableau et seuls les répondeurs complets avec un REGF inférieur au seuil discriminant de 120 fmol/mg protéine bé-néficiaient d'une longue survie ; il est à noter que les répondeurs complets avec un mauvais REGF n'avaient pas une survie significativement allongée par rapport aux répondeurs partiels. L'équipe de Grandis a intégré dans son analyse de la valeur pronostique du REGF la prise en compte de l'expression du ligand spécifique, le TGFα [17]. Leur étude a concerné un groupe de 91 patients traités par chirurgie et dont la tumeur primitive a été analysée pour son niveau d'expression en REGF et TGFα (immunohistochimie).…”
Section: Le Récepteur à L'egfunclassified
“…Studies have shown that an increased number of AgNORs is associated with increased tumor aggressiveness, i.e., the number of AgNORs per nucleus is higher in malignant than in benign tissues, higher in high-grade than in lowgrade malignancies, and higher in tumors with a poor prognosis than in those with a good prognosis. The presence of one to three AgNORs indicates normal tissue, that of more than four indicates oral SCC, and dysplasia is indicated by values between normal and SCC counts [1,3,24,25,28,33,36,39,40,46,47,50,59,64,80,81,82,83,84,93,95,96,99].…”
Section: Agnorsmentioning
confidence: 99%
“…There are 55 carcinogens in cigarette smoke which have been evaluated, and for which there is sufficient evidence of carcinogenicity in either laboratory animals of humans [57]. Cancer patients share the common high risk of developing a simultaneous or subsequent second primary cancer within this anatomical tract as a consequence of "field cancerization" [1,3,20,24,38,40,64], which refers to the potential development of cancer at multiple sites, a phenomenon observed during the development of oral cancer [74]. The development of second primary cancer in the upper aerodigestive tract may be due to diffuse mucosal initiation and promotion by exogenous carcinogen exposure such as tobacco and alcohol, placing the entire epithelial tissue at risk of tumorigenesis by a process called field cancerization or condemned mucosal syndrome [48,49,91].…”
Section: Field Cancerizationmentioning
confidence: 99%
“…An over expression of oncogenes (c-erbB, MDM2), an altered expression of suppressor genes (p53, p16, DCC) [1][2][3], and an abnormal expression of adhesion molecules (E-cadherin) has been reported as markers of a high malignant potential. Proliferation markers (Ki-67, AgNORs, PCNA) [4] and angiogenetic factors (VEGF, PD-ECGF/dThdPase) [5][6][7][8] are also related to the prognosis of the patients with various cancers including hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%